Coping strategies used by international students who recovered from homesickness and depression in Malaysia - Saravanan, Coumaravelou; Mohamad, Mardiana; Alias, Alizi (Elsevier, 2019)
International students use various self-help coping strategies to manage depression and home-sickness, but previous studies have not concluded on how international students have recoveredfrom depression and homesickness after using their self-help coping strategies. The aim of thisstudy is to use the semi structured interview to identify the self-help coping strategies used byinternational students who were unwilling to get treatment and had recovered from theirsymptoms of depression and homesickness in Malaysia. The second aim is to quantitativelyidentify the major psychosocial problems attributing to depression and homesickness amongstudents who have not recovered from the symptoms. Thirty-one international students out of520 diagnosed with depression and homesickness yet were unwilling to get treatment, wereinvited forthe reassessment of their homesickness and depressionafter three-and-a-halfmonths.Psychological assessment shows 9 students had recovered but 20 students had not. These ninestudents were interviewed to explore how they recovered from depression and homesickness.Meanwhile,the20studentswereaskedtocompleteaquestionnairewhichmeasuredtheirreasonfor not being able to recover from depression and homesickness. Results of the semi structuredinterview shows that some of the self-help coping strategies used by participants includingsharing their problems with others who were not experiencing homesickness and depression,keeping themselves busy with some useful activities, indulging in physical exercise, facing thesituation courageously, thinking positively, and reading and following some advice from re-ligious texts. The 20 students who did not recover faced more problems involving language,social connection, academic, loneliness, stress and family problems. Overall, self-help copingstrategies used by this study’s participants are useful in managing depression and homesickness.